Utilization of The Golden 1000 Application by Pregnant Women, Breastfeeding Women, Baduta Mothers, Cadres, and Midwives To Prevent Stunting in The Working Area Of The Bungursari Health Center in Tasikmalaya City in 2021 - Melsa Sagita Imaniar; Tatang Kusmana; Yuyun Solihatin (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
In 2020 there were 28 babies with stunted growth and 23 pregnant women with malnutrition at the Bungursari Health Center, with 56% of mothers providing exclusive breastfeeding and 74% of mothers starting from the age of 4 months of the baby and the menu given was not in accordance with WHO MPASI. This community service aims to use the golden1000 application for pregnant women, nursing mothers, mothers with children under 2 years old in guarding 1000 HPK so as to prevent stunting. Community Service using the golden1000 application was attended by 10 Bungursari PKM midwives, cibunigeulis village cadres and 15 third trimester pregnant women carried out for 2 days involving expert resource persons in their fields, namely the Golden1000 application Founder, Breastfeeding Counselor and PMBA Counselor. The training was carried out face-to-face and interactively using the golden1000 application and how to use it. The results obtained were an increase in the knowledge and skills of midwives, cadres and pregnant women in guarding 1000 HPK as well as with golden1000 application tools.